2018
DOI: 10.1001/jamanetworkopen.2018.1535
|View full text |Cite
|
Sign up to set email alerts
|

Use of Deep Learning to Examine the Association of the Built Environment With Prevalence of Neighborhood Adult Obesity

Abstract: Key Points Question How can convolutional neural networks assist in the study of the association between the built environment and obesity prevalence? Findings In this cross-sectional modeling study of 4 US urban areas, extraction of built environment (ie, both natural and modified elements of the physical environment) information from images using convolutional neural networks and use of that information to assess associations between the built environment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 61 publications
2
74
0
2
Order By: Relevance
“…After that point, the surrogate (that relies on detected cars) was not able to discriminate between different unemployment rates. This hints that an improved model could perhaps be produced if additional objects, besides cars, or even image features (similarly to [32]) are used for surrogate computation. This is one of our directions for future work in this area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that point, the surrogate (that relies on detected cars) was not able to discriminate between different unemployment rates. This hints that an improved model could perhaps be produced if additional objects, besides cars, or even image features (similarly to [32]) are used for surrogate computation. This is one of our directions for future work in this area.…”
Section: Discussionmentioning
confidence: 99%
“…In [30] the authors use GSV images to determine the number of pedestrians present in street segments in order to estimate pedestrian volume, while in [31] the authors automatically extract three measures of visual enclosure which are shown to be correlated with walkability. Moving even further, [32] uses features of the built environment, extracted through CNN and builds regression models that associate these features with adult obesity prevalence.…”
Section: Related Workmentioning
confidence: 99%
“…After that point, the surrogate (that relies on detected cars) was not able to discriminate between different unemployment rates. This hints that an improved model could perhaps be produced if additional objects, besides cars, or even image features (similarly to Reference [32]) are used for surrogate computation. This is one of our directions for future work in this area.…”
Section: Discussionmentioning
confidence: 97%
“…In Reference [30] the authors use GSV images to determine the number of pedestrians present in street segments in order to estimate pedestrian volume, while in Reference [31] the authors automatically extract three measures of visual enclosure which are shown to be correlated with walkability. Moving even further, Reference [32] uses features of the built environment, extracted through CNN and builds regression models that associate these features with adult obesity prevalence.…”
Section: Related Workmentioning
confidence: 99%
“…This increase in obesity prevalence is due to a complex interplay of biological, structural and individual factors (Hill and Peters, 1998;Nelson et al, 2006;Papas et al, 2007;Ogden et al, 2010). Factors such as public safety, socioeconomic status, and the neighborhood built environment may impact access to recreational facilities, and fresh, healthy foods (Freedman et al, 2002;Giles-Corti et al, 2003;Hill et al, 2003;Ellaway et al 2005;Gordon-Larsen et al, 2006;Lopez-Zetina et al, 2006;Mobley et al, 2006;Bennett et al, 2007;Papas et al, 2007;Casagrande et al, 2009;Maharana and Nsoesie, 2018). An individual's social environment can also influence health behaviors (such as, poor diet and physical inactivity) that are considered risk factors for obesity (Christakis and Fowler, 2007;McFerran et al, 2009;Yakusheva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%